The Interferon-induced Transmembrane Proteins, IFITM1, IFITM2, and IFITM3 Inhibit Hepatitis C Virus Entry - Narayana, Sumudu K. (J Biol Chem, 2015)
The interferon-induced transmembrane (IFITM) family of proteins have recently been identified as important host effector molecules of the type I interferon response against viruses. IFITM1 has been identified as a potent antiviral effector against hepatitis C virus (HCV), whereas the related family members IFITM2 and IFITM3 have been described to have antiviral effects against a broad range of RNA viruses. Here, we demonstrate that IFITM2 and IFITM3 play an integral role in the interferon response against HCV and act at the level of late entry stages of HCV infection. We have established that in hepatocytes, IFITM2 and IFITM3 localize to the late and early endosomes, respectively, as well as the lysosome. Furthermore, we have demonstrated that S-palmitoylation of all three IFITM proteins is essential for anti-HCV activity, whereas the conserved tyrosine residue in the N-terminal domain of IFITM2 and IFITM3 plays a significant role in protein localization. However, this tyrosine was found to be dispensable for anti-HCV activity, with mutation of the tyrosine resulting in an IFITM1-like phenotype with the retention of anti-HCV activity and co-localization of IFITM2 and IFITM3 with CD81. In conclusion, we propose that the IFITM proteins act in a coordinated manner to restrict HCV infection by targeting the endocytosed HCV virion for lysosomal degradation and demonstrate that the actions of the IFITM proteins are indeed virus and cell-type specific.